2011
DOI: 10.1155/2011/548327
|View full text |Cite
|
Sign up to set email alerts
|

Postcesarean Thromboprophylaxis with Two Different Regimens of Bemiparin

Abstract: Objectives. To compare the effectiveness of postcesarean thromboprophylaxis with two different regimens of bemiparin. Material and Methods. The study included 646 women with cesarean delivery in our hospital within a 1-year period, randomly assigned to one of two groups for prophylaxis with 3500 IU bemiparin once daily for 5 days or 3500 IU bemiparin once daily for 10 days. Results. There was one case of pulmonary embolism (first day following cesarean). An additional risk factor was present in 98.52% of the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…These results agree with the study findings done by [23], which found that VTE presents a significant risk for women requiring Caesarean section as well as Another study by [26], reported that 1067/5364 (20%) of the births had caesarean sections, five of those women (0.47%) developed symptomatic pulmonary embolism, and all of these women had additional risk factors for VTE. Cesarean delivery increases the risk of VTE because it involves pelvic surgery that may last > 30 minutes, adding to the prothrombotic effects of delivery, pregnancy weight gain, and other risk factors [27]. The findings of the existing, there was no significant link between medical history of hypertension, diabetes, heart disease, and lung diseases and VTE (P. value >0.05).…”
Section: Discussionmentioning
confidence: 88%
“…These results agree with the study findings done by [23], which found that VTE presents a significant risk for women requiring Caesarean section as well as Another study by [26], reported that 1067/5364 (20%) of the births had caesarean sections, five of those women (0.47%) developed symptomatic pulmonary embolism, and all of these women had additional risk factors for VTE. Cesarean delivery increases the risk of VTE because it involves pelvic surgery that may last > 30 minutes, adding to the prothrombotic effects of delivery, pregnancy weight gain, and other risk factors [27]. The findings of the existing, there was no significant link between medical history of hypertension, diabetes, heart disease, and lung diseases and VTE (P. value >0.05).…”
Section: Discussionmentioning
confidence: 88%
“…Fourteen studies including 11,944 patients were analyzed: eight randomized controlled trials ([RCTs] 8,001 patients) and six observational studies (3,943 patients). [27][28][29][30][31][32][33][34][35][36][37][38][39][40] Study characteristics are shown in Table 1, including each study's year of publication, county of origin, inclusion and exclusion criteria, characteristics of prophylactic anticoagulant studied, definition of primary outcome (VTE), duration of surveillance, and whether an unexposed comparator group was included. The results of the methodologic quality assessment are shown in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…A majority of studies in this analysis included only patients who underwent cesarean delivery (11/14, 78.6%), which is the most com-mon surgery performed in the United States, with a rate that continues to rise. [28][29][30][31][32][34][35][36][37][38]40 In a review of published evidence-based guidelines on VTE prevention in pregnant and postpartum patients, almost half of the guidelines (4/9) recommended initiation of thromboprophylaxis for people who undergo Unauthorized reproduction of this article is prohibited.…”
Section: Resultsmentioning
confidence: 99%
“…Operative delivery has been reported to place women at risk for VTE [ 5 , 16 - 18 ]. Most studies on thromboprophylaxis involved women who delivered via CS [ 19 , 20 ]. A previous study assessed thromboprophylaxis with unfractionated heparin in 116 parturients with varicose veins who delivered vaginally or by CS, and showed that unfractionated heparin significantly reduced the incidence of postpartum venous thrombosis [ 21 ].…”
Section: Discussionmentioning
confidence: 99%